K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

9 tháng 12 2018

a) \(\left(3x-3^4\right).7^5=3.7^7\)

\(3x-3^4=3.\left(7^7:7^5\right)\)

\(3x-3^4=3.7^2\)

\(3x-3^4=3.49\)

\(3x-81=147\)

\(3x=147+81\)

\(3x=228\)

\(x=228:3\)

\(x=76\)

b) \(4^{2x-5}-3.4^2=4^2\)

\(4^{2x-5}-3.16=16\)

\(4^{2x-5}-48=16\)

\(4^{2x-5}=16+48\)

\(4^{2x-5}=64\)

\(4^{2x-5}=4^3\)

\(2x-5=3\)

\(2x=3+5\)

\(2x=8\)

\(x=8:2\)

\(x=4\)

\(5^{2x-3}-2.5^2=5^2.3\)

\(5^{2x-3}-2.25=25.3\)

\(5^{2x-3}-50=75\)

\(5^{2x-3}=75+50\)

\(5^{2x-3}=125\)

\(5^{2x-3}=5^3\)

\(2x-3=3\)

\(2x=3+3\)

\(2x=6\)

\(x=6:2\)

\(x=3\)

9 tháng 12 2018

a,(3x-3^4).7^5=3.7^7        b,4^2x-3 -3.4^2=4^2             c,5^2x-3 -2.5^2=5^2.3

3x-3^4=(3.7^7):7^5             4^2x-3 -3.16=16                    5^2x-3-2.25=25.3

3x-81=3.7^2                         4^2x-3-48=16                       5^2x-3-50=75

3x-81=3.49                        4^2x-3=16+48                        5^2x-3=75+50

3x-81=147                           4^2x-3=64                            5^2x-3=125

3x=147+81                          4^2x-3=4^3                           5^2x-3=5^3

3x=228                                2x-3=3                                  2x-3=3

x=228:3                             2x=3+3                                  2x=3+3

x=76                                   2x=6                                      2x=6

Vậy=76                              x=6:2                                       x=6:2

                                         x=3                                         x=3

                                         Vậy x=3                              Vậy x=3

27 tháng 7 2019

\(27+\left(220-6x\right).3=615\)

\(\rightarrow\left(220-6x\right).3=615-27=588\)

\(\rightarrow220-6x=588:3=196\)

\(\rightarrow6x=220-196=24\)

\(\rightarrow x=24:6=4\)

27 tháng 7 2019

\(315-\left(x-3\right).7=210\)

\(\Rightarrow\left(x-3\right).7=315-210=105\)

\(\Rightarrow x-3=105:7=15\)

\(\Rightarrow x=15+3=18\)

18 tháng 10 2017

a, \(\left(2x+7\right)^4=10^{11}:10^7\)

\(\Rightarrow\left(2x+7\right)^4=10^4\)

\(\Rightarrow2x+7=10\)

\(\Rightarrow2x=10-7\)

\(\Rightarrow2x=3\)

\(\Rightarrow x=\dfrac{3}{2}\) hay \(x=1,5\)

b, \(5^{x-1}.7^{x-1}=25.49\)

\(\Rightarrow\)\(5^{x-1}.7^{x-1}=5^2.7^2\)

\(\Rightarrow\left\{{}\begin{matrix}5^{x-1}=5^2\\7^{x-1}=7^2\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}x-1=2\\x-1=2\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}x=3\\x=3\end{matrix}\right.\)

18 tháng 10 2017

c, \(\left(x-5\right)^{2018}=9.\left(x-5\right)^{2016}\)

\(\Rightarrow\dfrac{\left(x-5\right)^{2018}}{\left(x-5\right)^{2016}}=9.\dfrac{\left(x-5\right)^{2016}}{\left(x-5\right)^{2016}}\)

\(\Rightarrow\left(x-5\right)^2=9\)

\(\Leftrightarrow\left(x-5\right)^2=3^2\)

\(\Rightarrow x-5=3\)

\(\Rightarrow x=3+5\)

\(\Rightarrow x=8\)

3 tháng 7 2017

Ta có : (6x - 34) . 73 = 3.74

=> (6x - 34) = 3.7

=> (6x - 34) = 21

=> 6x - 81 = 21

=> 6x = 102 

=> x = 17

3 tháng 7 2017

<div style="position:relative;height:0;padding-bottom:56.25%"><iframe src="https://www.youtube.com/embed/koxpMVzDZhk?ecver=2" width="640" height="360" frameborder="0" style="position:absolute;width:100%;height:100%;left:0" allowfullscreen></iframe></div>

3 tháng 7 2017

2x - 23.32 = 138

2x - 72 = 138

2x = 138 + 72

2x = 200

x = 200 ÷ 2

x = 100

( 6.x - 34 ).73= 3.74

( 6x - 34 ).343 = 7203

6x - 34 = 7203 ÷ 343

6x - 34 = 21

6x = 21 + 34

6x =  55

x = 55 ÷ 6

x = 55/6

3 tháng 7 2017

a,2x-23.32=138

2x-72=138

2x=66

x=66:2

x=33

Vậy x=33

b,(6x-34).73=3.74

(6x-34).343=7203

6x-34=21

6x=21+34

6x=55

x=55:6

x=\(\frac{55}{6}\)

Vậy x=\(\frac{55}{6}\)

3 tháng 7 2017

a) \(2x-2^3.3^2=138\)

\(\Rightarrow2x=138+2^3.3^2\)

\(\Rightarrow2x=210\)

\(\Rightarrow x=105\)

Vậy x = 105.

3 tháng 7 2017

a)2x-96=138

2x=174

x=87

b)(6x-81).343=147

2058x-27783=147

2058x=27930

x=13,57